New Endophytic Fusarium spp. from Fraxinus excelsior Leaves in Slovakia - Ivanova, Helena; Malinicova, Lenka; Piknova, Maria; Pristas, Peter (Planta Medica, 2020)
Fraxinus excelsior is currently suffering from ash dieback disease caused by the fungus Hymenoscyphus fraxineus. Co-occurrence of large numbers of other fungi with endophytic as well as pathogenic lifestyles has been observed on F. excelsior. In this study, new endophytic Fusarium spp. isolate Fraxinus excelsior Fusarium from Slovak territory, associated with F. excelsior, was characterised. Using morphology-based approaches, the fungus was assigned to the genus Fusarium. The isolate formed thick-walled hyaline, fusiform, slightly curved macroconidia, produced from monophialides in sporodochia, pointed at the tip, mostly 3 – 5 septate, occasionally 6 septate, and 40 – 68 × 3.8 – 5.0 µm in size with basal pedicellate cells. For more accurate taxonomic affiliation, molecular sequence analyses of the internal transcribed spacer, translation elongation factor 1-alpha sequences, and partial β-tubulin gene were performed. While the internal transcribed spacer sequence of the isolate showed the highest similarity to the Fraxinus oxysporum species, translation elongation factor 1-alpha and partial β-tubulin sequences were distantly related to the Fraxinus avenaceum species. Based on these data, the Fraxinus excelsior Fusarium isolate could probably be considered a new species of the Fusarium genus.
Keywords: Oleaceae; Fusarium; endophyte; morphology; new species; phylogenetic analyses